2020
DOI: 10.3389/fnagi.2020.00251
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Hypoxia Accelerates the Onset of Alzheimer’s Disease Pathology in 5xFAD Mouse Model

Abstract: Alzheimer's disease (AD) is a chronic neurodegenerative disorder associated with cognitive impairment and later dementia among the elderly. Mounting evidence shows that adverse maternal environments during the fetal development increase the risk of diseases later in life including neurological disorders, and suggests an early origin in the development of AD-related dementia (ADRD) in utero. In the present study, we investigated the impact of antenatal hypoxia and fetal stress on the initiation of AD-related pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
(121 reference statements)
0
6
0
Order By: Relevance
“…The process was recorded by an overhead camera and analyzed offline. The travel distance was calculated by analyzing the recorded video using NIH image J software with the MouBeAT plugin as previously reported [59,60].…”
Section: Neurological Function Assessment and Brain Atrophy Assaymentioning
confidence: 99%
“…The process was recorded by an overhead camera and analyzed offline. The travel distance was calculated by analyzing the recorded video using NIH image J software with the MouBeAT plugin as previously reported [59,60].…”
Section: Neurological Function Assessment and Brain Atrophy Assaymentioning
confidence: 99%
“…reported that antenatal hypoxia increased the susceptibility of Alzheimer’s disease (AD) in the offspring of 5xFAD mice. 54 Similarly, we also discovered diminished cognitive performance in PH offspring through MWM, NOR, and step-through tests, however, the process requires further investigation. The hippocampus, which is required for spatial and episodic memory, is disrupted early in AD.…”
Section: Discussionmentioning
confidence: 64%
“…In addition, hypoxia has been identified as a significant contributor to the development of age-related neurodegenerative processes [20] since the brain is highly dependent on a continuous oxygen supply to sustain cellular homeostasis and energy metabolism. Hypoxic damage initiates accelerated cell aging [21,22]. Therefore, the functional response of cells to hypoxic exposure should be studied in the context of age-related changes.…”
Section: Of 17mentioning
confidence: 99%